2022
DOI: 10.1007/s00406-022-01420-w
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between genetic variation and gene expression of the glucocorticoid receptor gene NR3C1 and blood cortisol levels on verbal memory and hippocampal volumes

Abstract: The hypothalamus–pituitary–adrenal axis is the main physiological stress response system and regulating the release of cortisol. The two corticoid receptors encoded by the genes NR3C1 and NR3C2 are the main players in regulating the physiological response to cortisol. This biological system has been linked to neurocognitive processes and memory, yet the mechanisms remain largely unclear. In two independent general population studies (SHIP, total sample size > 5500), we aim to diseantangle the effects of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…In this study, we demonstrated that continuous intraperitoneal injection of CORT into mice reduced Lhcgr expression in GCs collected from developing follicles, especially the preovulatory follicles, indicating that CORT might impede ovulation in females by inhibiting Lhcgr expression in GCs. On the other hand, studies have shown that CORT accumulation can inhibit GnRH secretion and reduce LH levels [ 27 , 28 ]. In addition, glucocorticoids have been reported to directly inhibit LHβ expression in gonadal cells [ 36 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated that continuous intraperitoneal injection of CORT into mice reduced Lhcgr expression in GCs collected from developing follicles, especially the preovulatory follicles, indicating that CORT might impede ovulation in females by inhibiting Lhcgr expression in GCs. On the other hand, studies have shown that CORT accumulation can inhibit GnRH secretion and reduce LH levels [ 27 , 28 ]. In addition, glucocorticoids have been reported to directly inhibit LHβ expression in gonadal cells [ 36 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that cortisol injection in female mice significantly increase FasL expression in ovaries and impair oocyte competence by activating the Fas signaling and triggering apoptosis in MGCs, CCs, and oocytes [ 25 ]. In fact, the role of glucocorticoids is mediated by classic glucocorticoid receptors ( Nr3c1 ) [ 26 , 27 , 28 ]. Nr3c1 belongs to the nuclear receptor family and acts as a transcription regulator that can affect the function and recruitment of transcription factors [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%